Mongolian spots, a common congenital anomaly of the newborn. Topic review. - Romero-Parra, Laura Natalia (2022)
Dermal melanocytosis (DM), or Mongolian spot (MS), is the most common pigmented lesion in newborns, with a high prevalence in the Asian and black populations. These lesions apear when the melanocytes stop in their migration from the neural crest to the epidermis, giving rise to hyperpigmented lesions in the skin of the newborn that usually disappear during the first years of life, however, approximately 3% of these persist until adulthood. Most are located in the sacro-gluteal region, although they can also occupy extra sacral sites such as the head, face or flexor surface of the extremities. MM have commonly been considered a benign lesion, however, recent data suggests that they could appear in association with other pathological conditions, such as coexistence with inborn errors of metabolism, especially lysosmal storage diseases, but there is still not enough evidence  to correlate these conditions directly.